Case of Mistaken Identity: Pyogenic granuloma of chin is actually a draining dental fistula - Jerry E. Bouquot (Our Dermatology Online, 2015)
A 27 year old PHD student had an asymptomatic, slightly hemorrhagic, somewhat pedunculated skin mass of his chin surgically excised more than 3 times approximately 4 years earlier. A biopsy of the second recurrence showed the mass to be pyogenic granuloma. It recurred a 4th time but he could not afford further physician care so he grew a beard to hide the mass. After graduation and employment at a university he sought treatment of numerous cariously destroyed teeth.